2016
DOI: 10.1007/s13197-016-2322-9
|View full text |Cite
|
Sign up to set email alerts
|

Development and quality assessment of carrageenan incorporated low fat chevon patties

Abstract: The present study was conducted to develop and assess the quality of carrageenan incorporated chevon patties with the objective of reducing fat content. Efficacy of carrageenan as fat replacers (0.3, 0.6 & 0.9 %) was assessed for development of low fat chevon patties. Emulsion stability and cooking yield increased with the increase in levels of carrageenan. Significantly (P \ 0.05) lower fat and cholesterol contents and higher moisture and fat retention were observed in formulation with carrageenan. No signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…Based on the results obtained, the authors concluded that it was feasible to obtain low-fat chicken nuggets with sensory attributes and technological characteristics similar to conventional products. Nayak & Pathak (2016) also demonstrated that the carrageenan can be used successfully as a fat replacer in processed meat products. In this study, the authors assessed the quality of low-fat chevon patties reformulated with carrageenan (0.3%, 0.6% and 0.9%).…”
Section: Seaweeds and Compounds From Seaweeds As Replacers Of Fat In Meat Productsmentioning
confidence: 90%
“…Based on the results obtained, the authors concluded that it was feasible to obtain low-fat chicken nuggets with sensory attributes and technological characteristics similar to conventional products. Nayak & Pathak (2016) also demonstrated that the carrageenan can be used successfully as a fat replacer in processed meat products. In this study, the authors assessed the quality of low-fat chevon patties reformulated with carrageenan (0.3%, 0.6% and 0.9%).…”
Section: Seaweeds and Compounds From Seaweeds As Replacers Of Fat In Meat Productsmentioning
confidence: 90%
“…Since plant protein lacks the amino acid profile that humans require, ingredients like oat, lentil, and pea are added in combination to compensate (Bonke et al., 2020). Carrageenan was administered as a fat replacer at different concentrations to develop low鈥恌at chicken patties, which revealed significant changes in the textural properties, cooking yield, and emulsion stability (Nayak & Pathak, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The mineral profile analysis of the samples was performed with a slightly modified method by Nayak and Pathak (2016). The 1 g of the samples was digested in the microwave for 40 min.…”
Section: Methodsmentioning
confidence: 99%